A study on audit fees : Evidence from listed companies in Malaysia / Jeya Santhini Appannan - Appannan, Jeya Santhini (2012)
Audit fees charged in Malaysia were found to be the lowest in Asean countries. This situation raised questions on the factors influencing audit fees in Malaysia. The aim of this study is to investigate empirical factors that may influence the fees charged. This study examines the influences of auditees size, risk, complexity, auditor’s opinion, auditor’s size and non audit services on the fees. Researcher used mixed method to provide a more complete picture to attempt to achieve research objective and answer research questions set for this study. Interviews have been conducted with six respondents, which capture people’s experiences, hence, enabling contextualisation for the analysis of the issue. The overall finding of this study indicates that size and complexity being the most significant influence. As for risk, the ratio ‘inventory and receivables over total assets’ are significantly related to audit fees. This thesis concludes with several practical suggestions to help improve the study on audit fees in near future.